Depression, apathy and impaired self-awareness following severe traumatic brain injury: a preliminary investigation. (29th July 2019) - Bivona, U.; Costa, A.; Contrada, M.; Silvestro, D.; Azicnuda, E.; Aloisi, M.; Catania, G.; Ciurli, P.; Guariglia, C.; Caltagirone, C.; Formisano, R.; Prigatano, G.P.
ABSTRACT: Primary Objective : The primary aim of this study was to determine the frequency of severe impaired self-awareness (ISA) in patients with severe traumatic brain injury (TBI) and the correlates of selected clinical, neuropsychiatric and cognitive variables. The secondary aim of the study was to assess depression and apathy on the basis of their level of self-awareness. Methods : Thirty patients with severe TBI and 30 demographically matched healthy control subjects (HCs) were compared on measures of ISA, depression, anxiety, alexithymia, neuropsychiatric symptoms and cognitive flexibility. Results : Twenty percent of the patients demonstrated severe ISA. Severe post-acute ISA was associated with more severe cognitive inflexibility, despite the absence of differences in TBI severity, as evidenced by a Glasgow Coma Scale (GCS) score lower than 9 in all cases in the acute phase. Patients with severe ISA showed lower levels of depression and anxiety but tended to show more apathy and to have greater difficulty describing their emotional state than patients with severe TBI who showed minimal or no disturbance in self-awareness. Conclusion : These findings support the general hypothesis that severe ISA following severe TBI is typically not associated with depression and anxiety, but rather with apathy and cognitive inflexibility.